2017
DOI: 10.3847/1538-4357/aa93f0
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the New X-Ray Transient MAXI J1807+132: A Candidate of a Neutron Star Low-mass X-Ray Binary

Abstract: We report on the detection and follow-up multi-wavelength observations of the new X-ray transient MAXI J1807+132 with the MAXI/GSC, Swift, and ground-based optical telescopes. The source was first recognized with the MAXI/GSC on 2017 March 13. About a week later, it reached the maximum intensity (∼10 mCrab in 2-10 keV), and then gradually faded in ∼10 days by more than one order of magnitude. Time-averaged Swift/XRT spectra in the decaying phase can be described by a blackbody with a relatively low temperature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…We also note that Armas Padilla et al (2013b); Shidatsu et al (2017); Degenaar et al (2017) suggested the possible origin of the observed thermal emission in the X-ray spectra to be neutron star surface or the accretion disc. From Table 3, we observe that the obtained values of blackbody radius (2-3 kpc) are very similar to that have been found in other systems that are either proposed to be NS or are confirmed NS systems.…”
Section: Discussionmentioning
confidence: 71%
“…We also note that Armas Padilla et al (2013b); Shidatsu et al (2017); Degenaar et al (2017) suggested the possible origin of the observed thermal emission in the X-ray spectra to be neutron star surface or the accretion disc. From Table 3, we observe that the obtained values of blackbody radius (2-3 kpc) are very similar to that have been found in other systems that are either proposed to be NS or are confirmed NS systems.…”
Section: Discussionmentioning
confidence: 71%
“…Following previous works (e.g., Shidatsu et al 2017), we fixed r irr and f in , which were unconstrained with our data, at default values, 1.1 and 0.1, respectively, which are appropriate for the low/hard state spectra (Poutanen et al 1997). The other parameters were left as free parameters.…”
Section: Analysis Of Multi-wavelength Sedsmentioning
confidence: 99%
“…MAXI J1807+132 (hereafter MAXI J1807) was first discovered by the nova-alert system of the Monitor of All-sky X-ray Image Gas Slit Camera (MAXI /GSC; Matsuoka et al 2009;Mihara et al 2011) during its 2017 outburst (Negoro et al 2017). This detection was followed up with The Neil Gehrels Swift Observatory (Swift; Gehrels 2004) X-Ray Telescope (XRT; Burrows et al 2003) observations, spectral analysis of which suggested a LMXB with a NS primary (Shidatsu et al 2017). Further X-ray studies with XMM-Newton's European Photon Imaging Camera (EPIC;Strüder et al 2001) and ground-based optical telescopes supported the NS identification, although the possibility of a BH primary could not be ruled out (Jiménez-Ibarra et al 2019).…”
Section: Introductionmentioning
confidence: 98%